SOME INFORMATION ON THE STUDY OF KARAKALPAK CARPET ART - Доспанов О. Т; Сафаев М. М (TARIXIY TADQIQOTLAR, 2025)
The article examines the carpet art of the Karakalpak people, whose historical past is closely linked to nomadic culture. In this context, carpet weaving occupies a special place in folk art as a traditional artistic craft. Many Central Asian peoples attached significant importance to this direction, considering it not only in everyday life, but also as an important element that shapes unique art and reflects their inner philosophy and worldview. In this regard, special attention is paid to the extensive ethnocultural ties of the Turkic world. Carpet weaving with its characteristic decoration is an integral part of both historical processes and early traditions, transmitted in a geographical context from ancient nomadic cultures.